In vitro characterization of amino acid digestibility and fermentative properties of a specific hydrolyzed yeast, and its in vivo effects on growth performance and fecal microbiota in weanling piglets - Bravo de Laguna, Fernando; Achard, Caroline S.; Dunière, Lysiane; Parmentier, Elsa; Helmja, Katia; Bertaud, Bruno; Lebreton, Pierre; Saornil, David; Chevaux, Eric; Castex, Mathieu; Apper, Emmanuelle (Frontiers in Nutrition, 2025)
Weaning is a stressful event that is often accompanied by anorexia, risk of diarrhea, and development of intestinal disorders, making it crucial to provide highly digestible and palatable diets. Novel functional protein sources are being developed to be included in diets fed to weanling pigs. We evaluated in vitro and in vivo the properties of a recently developed hydrolyzed yeast protein source (Yela ProSecure; YPS; Lallemand SAS, Blagnac, France). The objectives were (1) to evaluate in vitro amino acids (AA) digestibility; (2) to assess, in vitro, the impact of the product’s insoluble fraction (YPSi) on the fermentative activity of piglet fecal microbiota; and (3) to test the effects of two inclusion levels (2.5 and 6%) on growth performance and fecal microbiota in weanling piglets. The total AA availability after 3 h of digestion was 76.6%, reaching 89.8% after 48 h. YPSi induced high gas and short-chain fatty acids production. In the in vivo experiment, a significant difference in body weight was observed on day 18 (p < 0.001) post-weaning and on day 40 (p < 0.05), with piglets in both YPS treatments being heavier than control piglets. A higher average daily feed intake was observed between weaning and day 18 (p < 0.01) and overall (p < 0.05) in both YPS treatments, and an improved feed conversion ratio was observed in both YPS treatments between weaning and day 18 (p < 0.001). Moreover, YPS significantly modulated the fecal microbiota composition after 2 days and 16 days of treatment, whereas no lasting effect was evidenced on day 40, namely after 19 days of withdrawal from the diet. Lower relative abundance (RA) of Campylobacterota (p adj. < 0.05) was evidenced in YPS groups compared to the control group. Furthermore, several members of the Lactobacillaceae family, annotated as L. amylovorus, L. mucosae, or L. reuteri, as well as Faecalibacterium prausnitzii, showed higher RA in YPS groups. To conclude, adding YPS to the diet of weanling piglets increased growth performance, probably due to nutrient absorption in the small intestine and its functional role on gut microbiota. Those results suggest complex interconnections between host and microbiota and emphasize the need to consider the holobiont theory when formulating a diet.